Adropin and insulin resistance: Integration of endocrine, circadian, and stress signals regulating glucose metabolism. Issue 11 (21st September 2021) - Butler, Andrew A.; Havel, Peter J.
Abstract: Dysregulation of hepatic glucose production (HGP) and glucose disposal leads to hyperglycemia and type 2 diabetes. Hyperglycemia results from the declining ability of insulin to reduce HGP and increase glucose disposal, as well as inadequate ß‐cell compensation for insulin resistance. Hyperglucagonemia resulting from reduced suppression of glucagon secretion by insulin contributes to hyperglycemia by stimulating HGP. The actions of pancreatic hormones are normally complemented by peptides secreted by cells distributed throughout the body. This regulatory network has provided new therapeutics for obesity and type 2 diabetes (e.g., glucagon‐like peptide 1). Other peptide hormones under investigation show promise in preclinical studies. Recent experiments using mice and nonhuman primates indicate the small secreted peptide hormone adropin regulates glucose metabolism. Here, recent expression profiling data indicating hepatic adropin expression increases with oxidative stress and declines with fasting or in the presence of hepatic insulin resistance and how adropin interacts with the pancreatic hormones, insulin, and glucagon to modulate glycemic control are discussed.